Investigation of biocompatibility and antibacterial properties of electrospun chitosan/ polyethylene oxide -based scaffolds containing propolis extract against Enterococcus faecalis, Pseudomonas aeruginosa, Staphylococcus aureus and Staphylococcus epidermidis - Sayed Reza Ebrahimi; Mohammad Nikbakht; Milad Shahini Shams Abadi; Abolfazl Gholipour; Mitra Bagheri; Majid Validi (Heliyon)
Bacterial infections represent a prevalent issue in healthcare settings. The indiscriminate use of antibiotics has contributed to the proliferation of antibiotic-resistant bacteria and complicating the treatment of such infections. Based on this, there arises a pressing need for alternative drugs to accelerate the treatment of a diverse array of Gram-negative and Gram-positive bacteria without inducing adverse side effects. In response to this need, we have developed chitosan (CS)/polyethylene oxide (PEO) nanofibers loaded with propolis extract using the electrospinning technique. We conducted an assessment of the antibacterial and antibiofilm activities of Chitosan/PEO nanofibers with varying concentrations of propolis against both Gram-positive and Gram-negative bacterial strains. The nanofibers demonstrated significant antibacterial activity against Staphylococcus aureus, Staphylococcus epidermidis, Enterococcus faecalis, and Pseudomonas aeruginosa. Additionally, according to the results obtained from the Congo red biofilm test, the optimal concentration of propolis in the nanofibrous mats exhibited a substantial antibiofilm effect against S. aureus, S. epidermidis, and E. faecalis. However, P.aeruginosa displayed growth and formed a relatively weak biofilm. The nanofiber scaffolds also demonstrated moderate antibiofilm activity against S. aureus, S. epidermidis, and E. faecalis, while displaying a weaker antibiofilm effect on Pseudomonas aeruginosa in the Tissue Culture Plate test. In summary, the biocompatible and antibacterial propolis extract-loaded Chitosan/PEO nanofibrous mats exhibit promising potential as effective wound dressings.